Modelling of adsorption isotherms of isomers using density functional theory. (18th June 2017) - Zimmermann, Patrick; Goetsch, Thomas; Zeiner, Tim; Enders, Sabine
ABSTRACT: For the separation of components having very similar vapour pressures, adsorption may be a promising separation method leading to products with a high purity. Especially, the separation of alkanes having the same molecular mass, but differ in the molecule architecture is very challenging and very important in petroleum refining. The adsorption isotherms of pure components and binary mixtures are calculated with the density functional theory, in which the thermodynamic properties are expressed as functionals of the spatially varying density, in combination with an equation of state based on the lattice cluster theory (LCT-EOS), which is originally developed by Freed and co-workers. The LCT-EOS allows to take the branching of the molecules directly into account without any additional fitting parameter. This theoretical framework can be employed for the calculation of the density profiles of pure components and partial density profiles in the case of mixtures within the narrow pores. The integration of these profiles leads to the adsorption isotherm. The obtained adsorption isotherms show that adsorption can be a promising technology for the separation of isomers having very similar boiling point, however further optimisation is required. Abstract :